1998
DOI: 10.1177/172460089801300307
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Carbohydrate Antigen 195 (CA195) and CEA Serum Levels as Prognostic Factors in Patients with Colorectal Cancer

Abstract: We evaluated in 214 patients with primary colorectal cancer the prognostic value of the preoperative serum levels of CEA and CA195. For CEA these levels were above the cutoff of 6 ng/ml in 31.3% of patients, whereas for CA195 they were higher than 12 U/ml in 35.9% of patients. The simultaneous use of both antigens increased the sensitivity to 49%, which was significantly higher than that of CEA (p < 0.001) and CA195 (p < 0.01) taken singly. The mean preoperative CEA levels were significantly (p < 0.001) correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There are some reports that serum CEA level is an independent risk factor for LMCRC. Patients with elevated CEA levels are more likely to develop recurrent disease and to have poorer overall survival than patients with normal CEA levels [ 19 , 20 ]. Our results are in agreement with this assessment.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports that serum CEA level is an independent risk factor for LMCRC. Patients with elevated CEA levels are more likely to develop recurrent disease and to have poorer overall survival than patients with normal CEA levels [ 19 , 20 ]. Our results are in agreement with this assessment.…”
Section: Discussionmentioning
confidence: 99%
“…CEA levels have previously been shown to be both a prognostic and predictive factor in multiple cancer types (Harrison et al , 1997; Andicoechea et al , 1998; Ebeling et al , 2002; Okamoto et al , 2005). In an evaluation of 214 patients with CRC, high pre-operative serum levels of CEA were associated with significantly reduced OS vs low serum CEA levels (Andicoechea et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of 214 patients with CRC, high pre-operative serum levels of CEA were associated with significantly reduced OS vs low serum CEA levels (Andicoechea et al , 1998). A retrospective analysis of 105 patients with NSCLC revealed that elevated baseline CEA levels significantly increased sensitivity to gefitinib treatment (Okamoto et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation